Adolescent help-seeking: an exploration of associations with perceived cause of emotional distress - O'Neill, Alisha; Stapley, Emily; Rehman, Ishba; Humphrey, Neil (Frontiers in Public Health, 2023)
Background Help-seeking is intrinsic to efforts to manage the onset, maintenance, or escalation of mental health difficulties during adolescence. However, our understanding of adolescent help-seeking remains somewhat nebulous. A greater comprehension of help-seeking behavior from the perspective of adolescents is needed. It is also prudent to explore help-seeking behavior in the context of perceived cause for emotional distress, particularly as causal beliefs have been found to influence help-seeking behavior in adults. Objectives The present study sought to categorize adolescents' experiences of help-seeking, and to examine the extent to which these categories (or “types”) of help-seeking behavior are associated with their perceptions of causal factors for emotional distress. Methods The data for this study were drawn from interviews conducted as part of the HeadStart Learning Programme. The sample comprised of 32 young people aged 11–12 years. Ideal-type analysis, a qualitative form of person-centered analysis, was used to construct a typology of adolescent help-seeking. Participants' help-seeking “type” was then compared with their perceived cause for emotional distress “type.” Findings We developed four distinct categories of help-seeking: (1) guided by others who have taken notice; (2) skeptical with unmet needs; (3) motivated and solution focused; and (4) preference for self-regulation. Simultaneously, we identified principal associations between perceived cause of emotional distress—(1) perceived lack of control; (2) unfair treatment; (3) others: their actions and judgements as the catalyst; (4) concern for self and others; and (5) self as cause—and help-seeking approaches. “Perceived lack of control” was most likely to be associated with “others who have taken notice”; “Unfair treatment” with “skeptical with unmet needs”; “others: their actions and judgements as the catalyst” with “motivated and solution focused”; “concern for self and others' with ‘guided by others who have taken notice”; finally, “self as cause” was most likely to be associated with “preference for self-regulation.” Conclusions This study demonstrates meaningful and distinct categories of adolescent help-seeking and offers empirical evidence to support the assertion that perceived cause for emotional distress may influence the help-seeking approaches of adolescents.